Development and characterization of a thermoreversible gel formulation of pregabalin for intranasal delivery - Mohananaidu, Keithanchali; Chatterjee, Bappaditya (2018)
INTRODUCTION: The complexity of the brain is a crucial ratelimiting factor in developing new drugs for the central nervous system (CNS). The blood–brain barrier and the blood–cerebrospinal fluid barrier play major role in restricting systemic drug delivery to the CNS. The unique neuronal connection of the nose and CNS, has given rise to intranasal drug delivery to brain bypassing the barriers. OBJECTIVES: This research aims to fabricate a thermoresponsive in situ gel drug delivery system for pregabalin, a neuropathic drug, via naso-mucosal route targeting brain. METHODS: A thermoresponsive in situ gel was developed by mixing 15-20% Poloxamer 407 with 0.15-0.25% Carrageenan to 1% pregabalin solution (weight ratio) by cold method. The formulations became liquid when stored at 2-8 ̊ C. The gelation temperature and pH for the in situ gels were 35-37 ̊ C and 6.0-6.5 respectively. Rheology study of the gel by a Haake-Mars programmable rheometer showed pseudoplasticity and distinct shear-thinning with increasing shear stress. CT3 Texture analyzer was used to determine the mucoadhesion strength of the gel using goat nasal mucosa. Ex-vivo drug permeation study through goat nasal mucosa was done using Franz diffusion cell. Pregabalin was quantified in formulation and ex-vivo permeated samples by a developed ATR-FTiR method. RESULTS: It was shown that only poloxamer containing gel had lesser mucoadhesion strength compared to that containing poloxamer-carrageenan both. Permeation flux was shown to be greater in case of thermoreversible gel compared to normal solution. This is because of higher retention of formulation on nasal mucosa. CONCLUSION: From in-vitro studies, it can be concluded that the in situ gelling system can result in higher nasal epithelial permeation, which could deliver drug to the brain efficiently. The brain distribution study of the drug using the developed in-situ gel is subjected to future in-vivo study in animal model.